Increasing Student Self-Openness Through Cyber Counselling Services with Reframing Techniques - Firanti Sukma Hardiyani Lubis; Ade Chita Putri Harahap (Journal of General Education and Humanities, 2025)
Students with a high level of self-openness are generally more capable of managing emotions and can formulate solutions to various problems faced. Self-openness includes the ability of individuals to know themselves deeply, which is reflected in the ability to convey information about themselves to others and the readiness to accept new perspectives or assessments about themselves. Students with good self-openness also tend to solve problems more effectively because they are willing to receive help and social support from their environment. In this case, self-openness allows a person to express the emotional burden to the other party, so that the pressure felt is not borne by oneself and feels lighter. The concept of self-disclosure focuses on sharing personal information, including biographical, thought, and emotional aspects previously unknown to others. In practice, self-openness includes delivering messages accompanied by verbal and non-verbal feedback that contributes to forming and maintaining the quality of interpersonal relationships. This research aims to increase self-openness in students of the 2022 batch of the Islamic Education Counselling Study Program at the State Islamic University of Medan. This study uses a quasi-experimental design of a group pre-test and post-test with a quantitative approach. Sampling was carried out purposively, and data were collected through the distribution of questionnaires. Data analysis was carried out using non-parametric statistical tests and the Wilcoxon signed-rank test, which resulted in an Asymp value. Sig was 0.042 (p < 0.05). These results indicate a significant difference between pre-test and post-test scores. Thus, it can be concluded that applying cyber counselling services with reframing techniques can increase students' self-openness.